(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the study of youth and the theoretical aspects of electoral technologies. Analysis of electoral technologies of political management through the prism of manipulative, normative, marketing, structural-functional, communicative and comparative approaches made it possible to present electoral technologies using the example of manipulation as a multidimensional socio-political phenomenon, as well as an integrated interdisciplinary system of knowledge